A Control-Based Multidimensional Approach to the Role of Optimism in the Use of Dementia Day Care Services. (November 2015) - Contador, Israel; Fernández-Calvo, Bernardino; Palenzuela, David L.; Campos, Francisco Ramos; Rivera-Navarro, Jesús; de Lucena, Virginia Menezes
We examined whether grounded optimism and external locus of control are associated with admission to dementia day care centers (DCCs). A total of 130 informal caregivers were recruited from the Alzheimer's Association in Salamanca (northwest Spain). All caregivers completed an assessment protocol that included the Battery of Generalized Expectancies of Control Scales (BEEGC-20, acronym in Spanish) as well as depression and burden measures. The decision of the care setting at baseline assessment (own home vs DCC) was considered the main outcome measure in the logistic regression analyses. Grounded optimism was a preventive factor for admission (odds ratio [OR]: 0.34 and confidence interval [CI]: 0.15-0.75), whereas external locus of control (OR: 2.75, CI: 1.25-6.03) increased the probabilities of using DCCs. Depression mediated the relationship between optimism and DCCs, but this effect was not consistent for burden. Grounded optimism promotes the extension of care at home for patients with dementia.